Efektivitas Pembelajaran Matematika melalui Penerapan Metode Field Trip pada Kelas VII - Hamzah Upu; Darwis; Athira (Issues in Mathematics Education (IMED), 2021)
This research aims to determine the effectiveness of learning mathematics through the application of the Field Trip method in class VII based on student learning outcomes, activity, and student responses. This research is quantitative approachwithpre-experimental study and sampling technique used is cluster random sampling. Data analysis technique used is descriptive and inferential analysis techniques. The results of descriptive analysis showed: (1) average results of students' pretest was 20,5(very lo category), average student posttest result was 77,7(high category) (2) the posttest results showed that classical completeness was reached student activity at 90% (18 students), (3) average normalized gain was 0.7(high category), (4) average student activity was 92% (very good category), (5) average percentage of students who gave positive response of 94%. Inferential analysis results show: (1) the average value of students after being taught with the fieldtrip learning method is greater than 70, (2) the normalized average gain value is greater than 0.3 (medium category), (3) the percentage of positive student responses greater than 70%. From the results of this study it can be concluded that learning by applying the Field Trip methods is effectively applied to students of grade VII.